Women and their Bone Health – Management with Homoeopathy and Diet (Homoeopathy for All, 2025)
Part of being a woman means paying attention to bone health throughout your life. There’s good reason for this: Your bones are likely smaller and thinner than a man’s, and as you approach menopause, your ovaries produce less and less estrogen, which causes your bone cells to break down. Women lose about half of their trabecular bone — the spongy tissue that fills your long bones — over a lifetime. Women also lose 30 percent of the denser tissue that covers bones. Most of the loss occurs within the first decade after menopause, but both men and women lose 0.5 percent of bone density every year after age 50.
Keywords: Symptoms; Osteoporosis